Quality of antiretroviral drugs, stavudine and indinavir capsules available in the Tanzanian market (Tanzania Medical Journal, 2007)
Background: The number of antiretroviral drugs (ARVs) available to HIV/AIDS patients in Tanzania is increasing due to a number of intervention programs such as PEPFAR and the Clinton Foundation. These ARVs are imported from a number of countries. However, currently there are no reports on the quality of these medicines imported into Tanzania. The sale of substandard and counterfeit drugs has been well documented particularly in developing countries. The marketing of counterfeit and substandard antiretroviral drugs has also been widely reported in Africa. It is therefore important to closely monitor the quality of ARVs marketed in Tanzania to ensure that substandard or fake products are uncovered before great harm is done to public health. Objective: To assess the quality of ARVs marketed in Tanzania.Methodology: A total of five samples of two generic drugs (stavudine and indinavir) from different manufacturers were randomly collected from various retail pharmacies. Assessment of package inserts and labels was carried out using the Tanzania Food and Drugs Authority (TFDA) specifications. The capsules were analyzed for the content of the active components using validated in-house methodsResults: All samples of Indinavir and Stavudine investigated conformed to the packaging and labeling specifications. However, all Indinavir samples were found to contain excess amount of active ingredient (112.6% - 118%) compared to the official limit of 95 – 105%. One sample of stavudine capsules failed the dissolution test, releasing only 56% instead of the specified 80% of the active ingredient.Conclusion: The results of this study emphasize the need for careful monitoring of the quality of drugs to ensure their safety and efficacy. Keywords: Antiretroviral drugs, Quality, Substandard drugs. Tanzania Medical Journal Vol. 21 (1) 2006: pp. 8-12